Comparison of Treatment Efficacy of Extracorporeal Shock Wave Lithotripsy and Pneumatic Ureteroscopic Lithotripsy for Lower Ureteric Stones (Medical Forum Monthly, 2021)
Objective: To compare the treatment efficacy of ESWL and pneumatic lithotripsy for lower Ureteric Stones at six weeks after the procedure.Study Design: A Randomized Controlled Trial StudyPlace and Duration of Study: This study was conducted at the Department of Urology at Shaikh Zayed Hospital Lahore from February, 2016 to August, 2016.Materials and Methods: A total 100 cases were included 50 in each group, after informed consent. By lottery method, patients were divided into group A or B. In group A ureteroscopic pneumatic lithotrips was performed with semi rigid 8 Fr ureterorenoscope. Swiss lithoclast was used for stone fragmentation. Prophylactic antibiotics were given to all patients. In group B, calculi were localized with fluoroscopy or ultrasound guidance in prone position and ESWL done. Analgesics were given to all patients. CT scan at 6 weeks follow-up was done to document complete stone clearance.Results: Total 100 cases with lower ureteric stone were included in this study. The mean age of the patients was 38±10.41 years (range 19-63 years). Male patients were more 72 (72%). When the treatment groups were compared there were more stone clearance in URSL group 44 (88%) and less in 33 (66%) (p 0.016).Conclusion: URSL was found to be more effective in terms of removal of lower ureteric stone as compared to ESWL.